Brain metabolite changes in patients with relapsing-remitting and secondary progressive multiple sclerosis: a two-year follow-up study - Obert, Dorothea Anna Maria; Diem, Ricarda (PLOS ONE, 2016)
Magnetic resonance spectroscopy (MRS) provides the unique ability to monitor several disease-related pathological processes via their characteristic metabolic markers in vivo. In the present study metabolic compositions were assessed every six months over the period of two years in 36 patients with Multiple Sclerosis (MS) including 21 relapsing-remitting (RR), 15 secondary progressive (SP) patients and 12 normal subjects. The concentrations of the main MRS-detectable metabolites N-acetylaspartate and N-acetylaspartylglutamate (tNAA), creatine and phosphocreatine (tCr), choline containing compounds (Cho), myo-Inositol (Ins), glutamine and glutamate (Glx) and their ratios were calculated in the normal appearing white matter (NAWM) and in selected non-enhancing white matter (WM) lesions. Association between metabolic concentrations in the NAWM and disability were investigated. Concentration of tNAA, a marker for neuroaxonal integrity, did not show any difference between the investigated groups. However, the patients with SPMS showed significant reduction of tNAA in the NAWM over the investigation period of two years indicating diffuse neuroaxonal loss during the disease course. Furthermore, we found a significant increase of Ins, Ins/tCr and Ins/tNAA in WM lesions independently from the course of the disease suggesting ongoing astrogliosis in silent-appearing WM lesions. Analyzing correlations between MRS metabolites in the NAWM and patients clinical status we found the positive correlation of Ins/tNAA with disability in patients with RRMS. In SPMS positive correlation of Cho with disability was found.